Assessment and data processing tools of inspiratory muscle fatigue evaluation using surface electromyography: a systematic review - da Gama, Alana Elza Fontes; Ferreira Filho, Antônio Francisco de Andrade; Rodrigues, Marco Aurélio Benedetti; de Andrade, Armèle Dornelas (Journal of Respiratory and CardioVascular Physical Therapy, 2014)
Objectives: To analyze inspiratory muscle fatigue using surface electromyography (SEMG). Methods: Searches were carried out in PUBMED, SCOPUS, CINAHL and SCIRUS databases by two researchers using the MeSH list keywords: electromyography, respiratory muscles and muscle fatigue. Complete cross-sectional studies in English, Portuguese and French from the last 10 years in which SEMG was used to analyze inspiratory muscle fatigue in humans were included. The Agency for Healthcare Research and Quality (AHRQ) scale was used to evaluate the quality of the studies. Results: 12 studies were selected, with total sample of 159 subjects (healthy or with respiratory disease) evaluated during exercise or inspiratory effort. Most studies assessed sternocleidomastoid muscles and some assessed the intercostals and diaphragm muscles. The most common signal processing was frequency analysis; root mean square, power and energy analyses were also found. Conclusion: Validation studies are needed for the standardization of SEMG on this muscle group and as well as myoelectrical signal processing in order to identify the most adequate form of analysis for different muscle activities.